2009
DOI: 10.1007/s10646-009-0413-3
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations in wetlands associated with coal-fired power plants

Abstract: There have been contradictory reports of the relative proportion of mercury from coal-fired power plants that deposits locally. Our objective was to determine any local effect of coal-fired power plants on total mercury concentrations in wetland sediment and tadpole samples. Four power plants and 45 wetlands were selected for study. Total mercury concentrations were determined in 75 sediment samples (range: 8-82 ng/g dry weight) and 100 bullfrog (Lithobates catesbeiana) and green frog (Lithobates clamitans) ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Hg‐enriched sediment cores were reported by Furl and Meredith () whereas Sackett et al () found that sunfish collected proximal to coal‐fired power plants had elevated tissue Se concentrations. In contrast, both Pinkney et al () and Weir et al () observed no evidence of increased THg tissue concentrations in fish and frog samples, respectively, in samples collected adjacent to coal power plants. The results from this study demonstrated no evidence of elevated concentrations of As, THg, MeHg, or Se in fish sampled proximal to coal‐fired Ohio River power plants.…”
Section: Discussionmentioning
confidence: 87%
“…Hg‐enriched sediment cores were reported by Furl and Meredith () whereas Sackett et al () found that sunfish collected proximal to coal‐fired power plants had elevated tissue Se concentrations. In contrast, both Pinkney et al () and Weir et al () observed no evidence of increased THg tissue concentrations in fish and frog samples, respectively, in samples collected adjacent to coal power plants. The results from this study demonstrated no evidence of elevated concentrations of As, THg, MeHg, or Se in fish sampled proximal to coal‐fired Ohio River power plants.…”
Section: Discussionmentioning
confidence: 87%
“…Areas downwind of coal-fired generating stations can be affected by local deposition of Hg; for example, Jardine et al (2009b) found declining concentrations of Hg in lichen from sites increasing in distance from a generating station in New Brunswick, Canada. However, the proximity of habitats to point sources of airborne Hg cannot explain all the variability observed in Hg concentrations among amphibians, fish, and freshwater invertebrates (Pinkney et al, 1997;Jardine et al, 2009b;Weir et al, 2010). Thus, it seems that while some systems will receive elevated inputs of Hg from nearby point sources, bacterial demethylation and localized factors such as wind patterns and the sensitivity of ecosystems are also important determinants of the concentrations of Hg that accumulate in food webs.…”
Section: Watershed Characteristics and Human Activitiesmentioning
confidence: 99%